Response of Various Stakeholders towards Newly Introduced Japanese Encephalitis Vaccine in a North Indian State. (2nd December 2014) - Kumar, Dinesh; Singh, Amar Jeet
Abstract : Introduction . Many attempts had been made to introduce newer vaccines into national immunization schedule of India. Special vaccines campaigns for diseases like JE were also initiated, which required a lot of preparation before vaccinating the beneficiaries. Objectives . To ascertain response of various stakeholders regarding launch of Japanese encephalitis vaccination campaign by state government in district Ambala, Haryana. Methodology . A 30-cluster survey was done to assess the vaccine coverage and views of the stakeholders. Various officials of state health services were also interviewed. Results . JE vaccine coverage was found to be 93.9%. Majority (59.8%) of the parents were informed about JE vaccination by the health worker. Many (83; 41.7%) parents said that they got their child vaccinated for JE since it "endangers life of children" and 82 (41.2%) said that "since everybody got it." All the staff was trained for JE vaccination campaign. Conclusion . JE vaccination campaign was a success with adequate preparation. Majority of people accepted vaccine in good faith in the government rather than due to their knowledge about disease.